Aberrant methylation of imprinted genes is associated with negative hormone receptor status in invasive breast cancer. Issue 3 (21st January 2015) - Barrow, Timothy M.; Barault, Ludovic; Ellsworth, Rachel E.; Harris, Holly R.; Binder, Alexandra M.; Valente, Allyson L.; Shriver, Craig D.; Michels, Karin B.
<x xml:space="preserve">Abstract</x> Epigenetic regulation of imprinted genes enables monoallelic expression according to parental origin, and its disruption is implicated in many cancers and developmental disorders. The expression of hormone receptors is significant in breast cancer because they are indicators of cancer cell growth rate and determine response to endocrine therapies. We investigated the frequency of aberrant events and variation in DNA methylation at nine imprinted sites in invasive breast cancer and examined the association with estrogen and progesterone receptor status. Breast tissue and blood from patients with invasive breast cancer (n = 38) and benign breast disease (n = 30) were compared with those from healthy individuals (n = 36), matched with the cancer patients by age at diagnosis, ethnicity, body mass index, menopausal status and familial history of cancer. DNA methylation and allele‐specific expression were analyzed by pyrosequencing. Tumor‐specific methylation changes at IGF2 DMR2 were observed in 59% of cancer patients, IGF2 DMR0 in 38%, DIRAS3 DMR in 36%, GRB10 ICR in 23%, PEG3 DMR in 21%, MEST ICR in 19%, H19 ICR in 18%, KvDMR in 8% and SNRPN/SNURF ICR in 4%. Variation in methylation was significantly greater in breast tissue from cancer patients compared with that in healthy individuals and benign breast disease. Aberrant methylation of three or more sites was significantly associated with negative estrogen‐alpha (Fisher's exact test, p = 0.02) and progesterone‐A (p = 0.02) receptor status. Aberrant events and increased variation in imprinted gene DNA methylation, therefore, seem to be frequent in invasive breast cancer and are associated with negative estrogen and progesterone receptor status, without loss of monoallelic expression.